NILAI-NILAI PENDIDIKAN KARAKTER ISLAM DALAM KISAH NABI MUSA BERGURU KEPADA NABI KHIDIR DALAM AL-QUR’AN SURAT AL-KAHFI AYAT 65-82 - Ridhowi, Ahmad; Muntaqo, Rifqi; Linnaja, Ngatho'ilah (AL-QALAM: JURNAL KEPENDIDIKAN, 2020)
The purpose of this study is to explore the values of Islamic character education in the content of the Al-Qur’an Surah Al-Kahf and take the wisdom contained in the letter related to Islamic character education. The type of research used is library research, a qualitative aproach with data sourch based on written works such as books of interpretation, data collection techniques using the maudhu’i method and tahlili method, data analysis techniques using content analysis and wacana analysis. The result o this study indicate that character education in the context of current education is relatively low due the several factors. The values o of character education contained in the story of prophet Musa studying with prophet Khidr in the Qur’an Surah Al-Kah verse 65-82 is: tawadhu’, patiently, sincerity and continuity in studying, social care, communicating well and polite, forgiving, tawaqal.